2003
DOI: 10.1086/376520
|View full text |Cite
|
Sign up to set email alerts
|

Cii* Absorption in Damped Lyα Systems. I. Star Formation Rates in a Two‐Phase Medium

Abstract: We describe a technique that for the first time measures star formation rates (SFRs) in damped Ly systems (DLAs) directly. We assume that massive stars form in DLAs and that the far-ultraviolet (FUV) radiation they emit heats the gas by the grain photoelectric mechanism. We infer the heating rate by equating it to the cooling rate measured by the strength of C ii* 1335.7 absorption. Since the heating rate is proportional to the product of the dust-to-gas ratio, the grain photoelectric heating efficiency, and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
261
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 160 publications
(292 citation statements)
references
References 68 publications
26
261
4
Order By: Relevance
“…5.4), the cooling rate scales with the dust-togas ratio (D/G), the photoelectric efficiency, and the FUV field. Since the latter is a good gauge of the star-formation rate (SFR) per unit physical area, the similar cooling rate between I Zw 18 and DLAs could in principle imply a similar surface SFR density (Wolfe et al 2003b). Following Bowen et al (2005), we can estimate the SFR from C * by using the Milky Way (MW) as a reference times lower than the MW value; Rémy et al, in prep.).…”
Section: Cooling Rate and Sfrmentioning
confidence: 99%
“…5.4), the cooling rate scales with the dust-togas ratio (D/G), the photoelectric efficiency, and the FUV field. Since the latter is a good gauge of the star-formation rate (SFR) per unit physical area, the similar cooling rate between I Zw 18 and DLAs could in principle imply a similar surface SFR density (Wolfe et al 2003b). Following Bowen et al (2005), we can estimate the SFR from C * by using the Milky Way (MW) as a reference times lower than the MW value; Rémy et al, in prep.).…”
Section: Cooling Rate and Sfrmentioning
confidence: 99%
“…Rafelski et al 2012). The excitation of different atomic and/or molecular species provides indirect constraints on instantaneous surface star-formation rates (SFRs Wolfe et al 2003;Srianand et al 2005;Noterdaeme et al 2007a,b). Prochaska & Wolfe (1997) tested a variety of models and concluded that the DLA kinematics, as traced by the profiles of low-ionisation metal absorption lines, could be characteristic of rapidly rotating discs.…”
Section: Introductionmentioning
confidence: 99%
“…Fynbo et al 2008). Nevertheless, DLA galaxies can provide substantial contributions to the global star formation rate (SFR) density at high redshifts (Wolfe et al 2003;Srianand et al 2005;Rauch et al 2008;Rahmani et al 2010). In addition, it has long been debated whether the kinematics of the absorbing gas, studied in terms of the velocity profiles of metal absorption lines, is more representative of that of large rotating galactic discs (Prochaska & Wolfe 1997) or small low-mass galactic clumps ) that build up hierarchically to form the galaxies known today (e.g.…”
Section: Introductionmentioning
confidence: 99%